Shape-preserved transformation of biological cells into synthetic hydrogel microparticles - Meyer, Kristin C (Adv Biosyst, 2019)
The synthesis of materials that can mimic the mechanical, and ultimately functional, properties of biological cells can broadly impact the development of biomimetic materials, as well as engineered tissues and therapeutics. Yet, it is challenging to synthesize, for example, microparticles that share both the anisotropic shapes as well as the elastic properties of living cells. Here we describe a cell-directed route to replicate cellular structures into synthetic hydrogels such as polyethylene glycol (PEG). First, the internal and external surfaces of chemically fixed cells are replicated in a conformal layer of silica using a sol-gel process. The template is subsequently removed to render shape-preserved, mesoporous silica replicas. Infiltration and crosslinking of PEG precursors and dissolution of the silica results in a soft hydrogel replica of the cellular template as demonstrated using erythrocytes, Hela, and neuronal cultured cells. We find that the elastic modulus can be tuned over an order of magnitude (~10-100 kPa) though with a high degree of variability. Furthermore, synthesis without removing the biotemplate results in stimuli responsive particles that swell/deswell in response to environmental cues. Overall this work provides a foundation to develop soft particles with nearly limitless architectural complexity derived from dynamic biological templates.